AUDIT KEPATUHAN PENGELOLAAN PIUTANG DALAM MEMINIMALISIR PIUTANG TAK TERTAGIH (Studi Kasus PT Bank Negara Indonesia (Persero) Tbk Cabang Makassar) - Ismawati Ismawati; Naidah Naidah; Linda Arisanty Razak (Universitas Muhammadiyah Makassar, 2020)
This research aims to know the application of the compliance audit in the management of accounts receivable accounts receivable to minimise not collectible at PT. Bank Negara Indonesia (Persero) Tbk. Makassar Branch. Methods of analysis used in this study is a qualitative method of analysis. In this case the researchers are using a risk-based audit approach, i.e. audit approach where checking is done against the harmony between the policy and the procedures are carried out with the provision of regulation. So, PT Bank Negara Indonesia (Persero) Tbk. Makassar Branch should be in line with regulations or procedures that have been held by Bank Indonesia (BI) in terms of financing. Based on the results of the study, pointed out that Compliance Audits conducted by the Director of compliance and Compliance Work Unit PT Bank Negara Indonesia (Persero) Tbk. Makassar Branch has gone well in accordance with the duties and those powers and keep independensinya properly because it had working guidelines, systems and procedures of work refers to the provisions of the applicable legislation. As well as in terms of the management of accounts receivable to the customer were in accordance with the applicable procedures. Each of these stages did not escape from the supervision of the compliance group so that each part or section associated on the stage professionally responsible.